Ekstraksi Kebutuhan Aplikasi Berdasarkan Feedback Pengguna Menggunakan Naïve Bayes dan Gamifikasi - Andre Rusli (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2018)
Requirements engineering is a series of activities which aims to elicit, analyze, evaluate, and document the requirements of a system that is being developed. The activities do not stop after the product is deployed but continues as the users use the product and provide feedbacks to the system and matter how decent the functionalities of a product are, if it cannot address the correct problem and/or opportunities of the stakeholders or users, the product cannot be considered useful. That being said, not all stakeholders are willing to participate in providing useful feedbacks to improve the product after deployment, for many reasons. Gamification is considered as an opportunity that can be utilized to improve the motivation of user to use a product by implementing game design elements into an existing software product, thus increasing user participation to contribute in providing useful feedbacks and evolving requirements of a software product. This research proposes a model to support engineers in motivating users to provide feedbacks using gamification and also Naïve Bayes Classifier to classify user feedbacks into categories needed by the developer to extract the requirements stated in the feedback, such as bug reports, feature request, user experiences, etc. Kata Kunci—requirements engineering, gamification, Naïve Bayes, user feedback